Environmental risk assessment for lead and mercury concentration in the Coricancha mining area of influence Chosica district - Güere Salazar, Fiorella Vanessa (2022)
The current investigation commission made it possible to assess the environmental risks of lead and mercury concentrations in the Coricancha mining area. The methods used were descriptive, three indicators of the sample for soil and two indicators of the sample for water were evaluated, all the derived results were contrasted with the Environmental Quality Standards. EPA analytical methods were used to analyze samples and determine the identity and concentration of a specific constituent in the samples. The results obtained for the soil indicate that it has Mercury with minimum values <0.02 mg / Kg and for Lead values between 77.19-96.01 mg / Kg, the results obtained for water indicate that it has Mercury with minimum values <0.001 mg / L and for Lead minimum values <0.006 mg / L., All the values found were within the permissible levels determined by the soil quality parameters for industrial use.